2009
DOI: 10.1111/j.1365-2133.2009.09220.x
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen and hydrogel-released ibuprofen in the reduction of inflammation-induced migration in melanoma cells

Abstract: These results demonstrate that TNF-alpha upregulated malignant melanoma migration in vitro and that this could be reduced by ibuprofen both in solution and delivered from a hydrogel. These effects of ibuprofen cannot be attributed simply to induction of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
1
26
0
3
Order By: Relevance
“…When compared to individual migration, collective migration, as in melanomas, presents higher dependence on cell-ECM adhesion [11]. In accordance with this statement, studies have shown that the presence of TNF-increased melanoma cell migration [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…When compared to individual migration, collective migration, as in melanomas, presents higher dependence on cell-ECM adhesion [11]. In accordance with this statement, studies have shown that the presence of TNF-increased melanoma cell migration [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 57%
“…Experimental data used on calibration were based on the work by Redpath et al [15]. Data were obtained from a study using C8161 human cutaneous melanoma, in control media culture and under the influence of pro-inflammatory cytokine TNF-.…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico results were then compared with the ones collected experimentally in water and in hydrogel environments. The drug investigated in this work is sodium ibuprofene (IP), a member of non-steroidal anti-inflammatory drugs, commonly used for relief from arthritis, fever and as a generic pain reliever [33][34][35] . The chosen hydrogel, specifically developed for central nervous system repair strategies, was obtained by synthesis from statistical block polycondensation between agarose and carbomer 974P (briefly termed as AC, acronymic of their main components), together with cross-linkers 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…Um efeito muito similar na redução da migração, também foi observado em células de melanomas, tratadas com ibuprofeno (Redpath et al, 2009). Ensaios de transwell e de monocamada mostraram uma diminuição na migração em câncer de próstata tratada com AINEs (Wynne e Djakiew, 2010).…”
Section: Análise Da Expressão Da Proteínaunclassified